An investigation of aerogels, foams, and foils for multi-wire proportional counter neutron detectors - Nelson, Kyle (Kansas State University, 2013)
The 3He gas shortage for neutron detection has caused an increase in research efforts to develop viable alternative technologies. 3He neutron detectors cover areas ranging from 10–1000 cm2 in cylindrical form factors and are ideal for many nuclear applications due to their high intrinsic thermal neutron detection efficiency (> 80%) and gamma-ray discrimination (GRR ≤ 1 x 10-6) capabilities. Neutron monitoring systems for nuclear security applications include Radiation Portal Monitors (RPM’s), backpack, briefcase, and hand-held sensors. A viable replacement technology is presented here and compares three neutron detectors, each with different neutron absorber materials, to current 3He standards. These materials include Li and/or B silica aerogels, LiF impregnated foams, and metallic Li foils. Additionally, other neutron absorbing materials were investigated in this work and include LiF coated Mylar, B foils, BN coated carbon foam, and BN coated plastic honeycomb. From theoretical calculations, the Li foil material showed the greatest promise as a viable 3He alternative, thus a majority of the research efforts were focused on this material. The new neutron detector was a multi-wire proportional counter (MWPC) constructed using alternating banks of anode wires and 95% enriched 6Li foils sheets spaced 1.63 cm apart. In total, six anode banks and five layers of foil were used, thus an anode wire bank was positioned on each side of a suspended foils. Reaction products from the 6Li(n,α)3H reaction were able to escape both side of a foil sheet simultaneously and be measured in the surrounding gas volume concurrently. This new concept of measuring both reaction products from a single neutron absorption in a solid-form absorber material increased the intrinsic thermal neutron detection efficiency and gamma-ray discrimination compared to coated gas-filled detectors. Three different sizes of Li foil MWPC neutron detectors were constructed ranging from 25–1250 cm2 and included detectors for RPM’s, backpacks, and hand-held systems. The measured intrinsic thermal neutron detection efficiency of these devices was approximately 54%, but it is possible to exceed 80% efficiency with additional foils. The gamma-ray discrimination abilities of the detector exceeded 3He tubes by almost three orders of magnitude (GRR = 7.6 x 10-9).
Keywords: Neutron detector; Lithium foil; Foam; Multi-wire proportional counter; Aerogel